2015
DOI: 10.1038/jid.2015.62
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Association Study Identifies the Skin Color Genes IRF4, MC1R, ASIP, and BNC2 Influencing Facial Pigmented Spots

Abstract: Facial pigmented spots are a common skin aging feature, but genetic predisposition has yet to be thoroughly investigated. We conducted a genome-wide association study for pigmented spots in 2,844 Dutch Europeans from the Rotterdam Study (mean age: 66.9±8.0 years; 47% male). Using semi-automated image analysis of high-resolution digital facial photographs, facial pigmented spots were quantified as the percentage of affected skin area (mean women: 2.0% ±0.9, men: 0.9% ±0.6). We identified genome-wide significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
151
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(163 citation statements)
references
References 55 publications
7
151
3
2
Order By: Relevance
“…In the analysis of skin cancer, variants in or near IRF4 (MIM: 601900), MC1R (MIM: 155555), RALY (MIM: 614663), and SLC45A2 (MIM: 606202) were significant at a ¼ 5 3 10 À8 , and all four of these genes were previously identified as associated with pigmentation traits and skin cancers. [31][32][33][34][35][36] In the other traits, variants in TCF7L2 (MIM:…”
Section: Analysis Of Mgi Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In the analysis of skin cancer, variants in or near IRF4 (MIM: 601900), MC1R (MIM: 155555), RALY (MIM: 614663), and SLC45A2 (MIM: 606202) were significant at a ¼ 5 3 10 À8 , and all four of these genes were previously identified as associated with pigmentation traits and skin cancers. [31][32][33][34][35][36] In the other traits, variants in TCF7L2 (MIM:…”
Section: Analysis Of Mgi Datamentioning
confidence: 99%
“…Zhang et al 31 Sulem et al, 32 Jacobs et al, 33 and Liu et al 34 5:33951693 rs16891982 SLC45A2 C>G 0.038 7 3 10…”
Section: à13mentioning
confidence: 99%
“…Loss-of-function MC1R alleles has been associated with the presence of solar lentigines, suggesting that melanocytes with reduced MC1R activity are expected to form these benign hyperpigmented lesions (37,97). Genetic variants in the SLC45A2 gene have also been found to be implicated in solar lentigines development (98), although this correlation was not found in a GWAS study using Caucasian individuals (30). This high-powered GWAS study demonstrated significant associations between variants in four pigmentation-related genes (IRF4, MC1R, ASIP and BNC2) and facial pigmented spots, including solar lentigines among others (30).…”
Section: Lentiginesmentioning
confidence: 99%
“…Furthermore, Jacobs and cols. (2015) showed that females presented a much higher prevalence of facial sun spots than males, suggesting that females are more severely affected by sun exposure than males independently of genotype (30). These differences could be the result of socio-cultural reasons, as males tend to spend more time outdoors; physiological reasons, as males have thicker skin and increased number of blood vessels; differential tanning, as no sex difference in basal skin pigmentation has been shown; and hormonal factors, as oestrogens stimulate pigmentation while androgens have an inhibitory effect on melanocytes (61,87).…”
Section: Letter To the Editormentioning
confidence: 99%
See 1 more Smart Citation